Encounters with Jesus : unexpected answers to life's biggest questions - Keller, Timothy, 1950- (Dutton, Penguin Group USA, 2013)
What is my purpose in life? What is a good life? Why is there so much wrong with our world? What can I do to help make it right? These are some of the big questions that everyone must answer. And any lasting change in our lives will start with a change to one or more of our answers to these questions. Jesus changed the life of every person he met in the Gospels, through powerful experiences and words that led them to unexpected and transforming answers to their big questions. These conversations can still address our questions and doubts today. Originally published as an eSeries, Encounters with Jesus focuses on several of these meetings--including with a skeptical student, a religious insider, an outcast, even Jesus' mother--and shows how the central events in Jesus' life provide ways for us to encounter him again or for the first time.--From publisher description.